PENGARUH BUDAYA BIROKRASI TERHADAP EFEKTIVITAS PELAYANAN APARATUR BADAN KESATUAN BANGSA POLITIK DAN PERLINDUNGAN MASYARAKAT - MUSDAR, ANDI ZULQIFLY; PANGKEY, MASJE SILIJA; POMBENGI, JERICHO DANGA (JURNAL ADMINISTRASI PUBLIK, 2017)
This research describes two variables, namely bureaucratic culture and effectiveness of service apparatus. The purpose ofthis study is to determine the influence of bureaucratic culture on the effectiveness of apparatus services. Bureaucraticcultural variables were tested using 6 indicators. Variables of service effectiveness of apparatus were tested using 3dimension. This research was conducted in the office of National Unity and Political Protection Agency of Manado City.The research method used is quantitative, with data collection techniques distributing questionnaires to respondents. Thesample of this research is 41 employees of National Unity and Community Protection Agency of Manado City. The dataanalysis used is spearman rank correlation and simple linear regression using SPSS for ios. The result of spearmancorrelation coefficient correlation between bureaucracy culture and effectiveness of service apparatus is +0,467. Whichmean indicates a significant correlation. While the "+" sign indicates that the direction of the positive relationship. Fromthe results of simple regression calculation can be obtained significance value of bureaucratic cultural variables is of 0.001smaller than 0.05 then bureaucratic culture has a significant effect on the effectiveness of apparatus services. It can beconcluded that bureaucratic culture variable with effectiveness variable of apparatus service shows that bureaucraticculture variable has significant correlation and direction of positive or unidirectional relationship. The result of the analysisalso shows that bureaucratic culture variable has significant influence on the effectiveness variable of apparatus service,so it can be concluded that bureaucratic culture has significant influence on the effectiveness of apparatus service at BadanPersatuan Bangsa Politik and Perlindungan Masyarakat in Manado City.Keywords: Bureaucratic Culture, Effectiveness of Apparatus Services.